2021
DOI: 10.1002/chem.202005016
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Chiral Tetrakis‐Iodo‐Triazole Halogen‐Bond Donor for Chiral Recognition and Enantioselective Catalysis

Abstract: Halogen bonding represents a powerful tool in the field of noncovalent interactions. However, applications in enantioselective recognition and catalysis remain almost nonexistent, due in part to the distinct features of halogen bonds, including long covalent and noncovalent bond distances and high directionality. Herein, this work presents a novel chiral tetrakis‐iodo‐triazole structure as a neutral halogen bond donor for both chiral anion‐recognition and enantioinduction in ion‐pair organocatalysis. NMR‐titra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 83 publications
0
37
1
5
Order By: Relevance
“…Beside crystal engineering [76,77] and recognition studies, [19] organocatalysis is by now one the most important fields in which iodine(I)‐based halogen bonding is utilized [78–80] . In the last decade, it has emerged as an interesting alternative to hydrogen bonding, with recent examples showing successful induction of chirality [81,82] . While the first successful XB based organocatalyses employed neutral iodine(I) species with polyfluorinated backbones like 20 (Scheme 6), [83,84] by now mostly cationic heteroaryl backbones like (benz)imidazolium or triazolium ions are used, as they provide much higher activity [78–80] .…”
Section: Applications In Organocatalysismentioning
confidence: 99%
“…Beside crystal engineering [76,77] and recognition studies, [19] organocatalysis is by now one the most important fields in which iodine(I)‐based halogen bonding is utilized [78–80] . In the last decade, it has emerged as an interesting alternative to hydrogen bonding, with recent examples showing successful induction of chirality [81,82] . While the first successful XB based organocatalyses employed neutral iodine(I) species with polyfluorinated backbones like 20 (Scheme 6), [83,84] by now mostly cationic heteroaryl backbones like (benz)imidazolium or triazolium ions are used, as they provide much higher activity [78–80] .…”
Section: Applications In Organocatalysismentioning
confidence: 99%
“…4e Notably, in 2018 the Arai group used a bifunctional alkaloid-based XB catalyst to carry out an asymmetric Mannich reaction, 5a in 2020 the Huber group carried out the rst solely XB-catalysed asymmetric reaction using the Mukaiyama-aldol reaction as a model 21 and in 2021 the Mancheño group demonstrated that a neutral tetrakis-iodo-triazole can be used as an asymmetric XB catalyst in the Reissert-type dearomatization of quinolone. 22 We envisioned that the bifunctional alkaloid-based XB catalyst could be used to activate vinyl phosphonates in a Michael reaction with a nucleophile. Achieving this would both expand the chemical space of asymmetric XB catalysis and that of optically active phosphorus chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…4 e Notably, in 2018 the Arai group used a bifunctional alkaloid-based XB catalyst to carry out an asymmetric Mannich reaction, 5 a in 2020 the Huber group carried out the first solely XB-catalysed asymmetric reaction using the Mukaiyama-aldol reaction as a model 21 and in 2021 the Mancheño group demonstrated that a neutral tetrakis-iodo-triazole can be used as an asymmetric XB catalyst in the Reissert-type dearomatization of quinolone. 22 …”
Section: Introductionmentioning
confidence: 99%
“…A variety of XB donors bearing strong electron‐withdrawing moieties such as perfluoroaryls [8] and heterocycles [9] have been developed to facilitate reactions through XB for electron‐rich species and functional groups. Anion‐binding catalysis through XB is a typical example (Figure 1), the ability of which was evaluated in the reaction of 1‐chloroisochroman [7e,g] (Scheme 1a) and quinoline/isoquinoline [8e,9i] (Scheme 1b). We recently reported the use of commercially available perfluoroiodobenzene (C 6 F 5 I) as an XB‐driven anion‐binding catalyst that efficiently promoted the allylation, crotylation, and prenylation of in situ‐ generated N ‐activated heteroaromatics with silatrane nucleophiles (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%